Pro Git - Chacon, Scott (Apress : Imprint: Apress, 2009)
Git is the version control system developed by Linus Torvalds for Linux kernel development. It took the open source world by storm since its inception in 2005, and is used by small development shops and giants like Google, Red Hat, and IBM, and of course many open source projects. A book by Git experts to turn you into a Git expert Introduces the world of distributed version control Shows how to build a Git development workflow.